Augmented Reality for Quechua Language Teaching-Learning: A Systematic Review - Cardenas-Valdivia, Jhonatan (2023)
With the passage of time, the advancement of technology is evident, Augmented Reality (AR) is an innovative technological tool that has emerged and has been highly attractive to users, allowing the sharing of information in a dynamic and realistic way. In the present systematic literature review (SLR), a search was conducted for manuscripts published in 6 databases between the years 2017 to 2022, related to the implementation of AR to improve the teaching-learning (TL) process of the Quechua language, which were analyzed and systematized using the Prisma methodology, resulting in 56 manuscripts that supported answering the research questions, where the various factors that allow improving the TL process of the Quechua language and the various benefits generated by its implementation were identified. It is concluded that, according to the results, the application of AR in the TL of the Quechua language is an efficient and productive tool; however, it can also be a source of distraction in the study, so it is necessary to have good management of this methodology and the study environment to obtain better achievements. For this reason, we propose a model that serves as a basis for proper management in the application of AR to improve the process of the Quechua TL language.